1995
DOI: 10.1002/edp.2430040406
|View full text |Cite
|
Sign up to set email alerts
|

Persistent crying and parenting: Search for a butterfly in a dynamic system

Abstract: The risks and c a m of persistent crying in early infancy are discussed on the basis of a study of 61 infants referred to the Munich Interdisciplinary Research and Intervention Program for Fussy Babies for persistent crying between 1 and 6 months of age, and of a community sample of 51 infants of the same age. Particular attention was paid to pre-verbal parent-infant communication, the development of which was interpreted in terms of a dynamic interactional system including both regulatory and communicative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 44 publications
2
48
0
4
Order By: Relevance
“…It is apparent that synchronization of the sleep/wake cycle also emerges with increasing IC, but there is no clear-cut pattern of sleep in infants with IC compared to healthy controls. Whereas Kirjavainen et al [13] observed no statistical difference in objectively assessed sleep duration or fragmentation between infants with and without IC over a period of 24 h, others have reported decreased sleep during the day [14,15]. These conflicting results may reflect methodological differences insofar as both subjective (i.e.…”
Section: Introductionmentioning
confidence: 46%
See 2 more Smart Citations
“…It is apparent that synchronization of the sleep/wake cycle also emerges with increasing IC, but there is no clear-cut pattern of sleep in infants with IC compared to healthy controls. Whereas Kirjavainen et al [13] observed no statistical difference in objectively assessed sleep duration or fragmentation between infants with and without IC over a period of 24 h, others have reported decreased sleep during the day [14,15]. These conflicting results may reflect methodological differences insofar as both subjective (i.e.…”
Section: Introductionmentioning
confidence: 46%
“…Raiha et al [30] assumed that these dysfunctional behaviors had probably emerged as a result of infant's crying behavior and not vice versa. Papousek and von Hofacker [15] reported increased scores of depression, exhaustion, frustration, anger and anxious overprotection in mothers with infants with IC relative to mothers with infants without IC. In this vein, St James-Roberts et al [31] found that mothers with infants suffering from IC had higher scores for depressive symptoms compared to mothers of infants without IC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Early RPs may be associated with trajectories of dysregulation into childhood 4 and subsequent cognitive, behavior and attention problems, [5][6][7][8][9][10][11] especially if crying or feeding problems persist beyond the age of 3 to 4 months. [1][2][3]6,[12][13][14] In addition, multiple RPs, i.e. having two or three single RPs at the same time, increases the likelihood of later behavior problems.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, infants with colic were found to look "typical" in their responses to aversive stimuli after the colic was resolved (Stifter & Braungart, 1992). On the other hand, investigations on the outcomes of colic suggest that excessive crying in early infancy represents the extreme on a temperamental continuum (Carey, 1972;Jacobson & Melvin, 1995;Lehtonen, Korhonen, & Korvenranta, 1994) or is the result of continued insensitive, overstimulating parenting (Papoušek & von Hofacker, 1995). Interestingly, in one study infants with "persistent crying" were found to show stability in negative reactivity immediately after the colic resolved, but no differences were observed several months later (St. James Roberts, Conroy, & Wilsher, 1998b).…”
mentioning
confidence: 99%